Studi Eksperimental Pengaruh Jumlah Sudu terhadap Daya pada Turbin Angin Sumbu Vertikal Tipe Rotor Crossflow untuk Optimalisasi Angin di Wilayah Pantai Kota Balikpapan - Rizianiza, Illa; Herfandi, Diky (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2020)
Wind energy was one of the renewable energy alternatives with the biggest potential in Indonesia to be used as a power plant. Balikpapan is an area with extensive coastal areas with great wind potential. Vertical Axis Wind Turbine (VAWT) is an upright axis wind turbine whose movement of the shaft and rotor is parallel to the direction of the wind so that the rotor can rotate in all wind directions. Crossflow type VAWTis a type of VAWT that can operate at low wind speeds have a starting torque and a high value of power efficiency. VAWT is designed with specifications of rotor diameter 500 mm, rotor height 500 mm, 1:1 aspect ratio, 90o curvature angle, and length of blade 75 mm. The variations of the number of blades used are 8, 12, and 16 blades. The results showed that the number of blades affected the power produced by the wind turbine. VAWT with the number of blades 16 is the best performing turbine with the highest power value of 10,325 mW at a wind speed of 3,05 m/s. The best and optimal performance found in the variation of the number of blades 16. It is obtained a maximum CP value of 0,00273 at Tip Speed Ratio 0,578 and maximum CT value of 0,00485 at Tip Speed Ratio 0,496 so VAWT with the number of blades 16 is the most optimal wind turbine to be applied at Manggar Beach, Balikpapan City.